Isolation and partial characterization of a fatty acid binding protein in rat liver plasma membranes. - Stremmel, W (1985)
When [14C]oleate-bovine serum albumin complexes were incubated in vitro with rat liver plasma membranes (LPM), specific, saturable binding of oleate to the membranes was observed. Maximal heat-sensitive (i.e., specific) binding was 3.2 nmol/mg of membrane protein. Oleate-agarose affinity chromatography of Triton X-100-solubilized LPM was used to isolate a single 40-kDa protein with high affinity for oleate. On gel filtration, the protein comigrated with various fatty acids but not with [14C]bilirubin, [35S]sulfobromophthalein, [14C]taurocholate, [14C]phosphatidylcholine, or [14C]cholesteryloleate. A rabbit antibody to this membrane fatty acid-binding protein gave a single precipitin line with the antigen but no reactivity with concentrated cytosolic proteins, LPM bilirubin/sulfobromophthalein-binding protein, or rat albumin or other rat plasma proteins. The antibody selectively inhibited heat-sensitive binding of [14C]oleate to LPM. Immunofluorescence studies localized the antigen in liver-cell plasma membranes as well as in other major sites of fatty acid transport. These data are compatible with the hypothesis that this protein may act as a receptor in a hepatocellular uptake mechanism for fatty acids.